AYURVEDIC APPROACH TO SHOTHA VYADHI WSR TO CHRONIC KIDNEY DISEASE - Thote, Pranali; Chandurkar, Vivek (International Journal of Research -GRANTHAALAYAH, 2018)
A 75 yrs male patient presenting with ubhaypadshoth (bilateral pedal edema), alpa udarvriddhi (abdominal distention), dourbalya (generalized weakness), agnimandya (loss of appetite) diagnosed as shotha vyadhi (odema) was brought to SSNJ Ayurved Hospital, Solapur. Patient was treated with an integrated approach of ayurveda. According to ayurveda, treatment of is vatanulomak aushadhi (laxative), agnideepan (increase appetite), balaprapti (stimulant for hepatic function), lepachikitsa, Proper diet (cow milk) and external application of shothahara lepa. Appreciable results were observed in the form of reduction in abdominal girth, decreased pedal edema,increased appetite, increased strength and significant changes in investigations.